Failure behaviour of a fire protected steel element - Georgios Drosopoulos; Siphesihle Motsa (Fracture and Structural Integrity)
In the present article the failure behaviour of a steel, beam type element supported against fire by protection boards, is studied. Three – dimensional, coupled temperature - displacement, non-linear finite element analysis models have been developed to simulate the unprotected and protected structure. A simple modelling approach is proposed for the investigation of the influence of the gradual failure of fire protection at elevated temperatures, on the structural performance of the system, under thermal and mechanical loads. Yielding of steel is depicted and force – displacement diagrams are used to evaluate the ultimate behaviour of the unprotected and protected models. It is shown that for the protected structure, yielding is less severe and the time period up to maximum strength is significantly longer. Eventually, is depicted how failure of the fire protection leads to a gradual reduction of the response, in fire conditions.